PENERAPAN OMKERING VAN BEWIJSLAST DALAM PEMBUKTIAN TINDAK PIDANA KORUPSI INDONESIA - Mery R.L Sibarani (Fakultas Hukum Universitas Kristen Indonesia, 2023)
In criminal procedural law, criminal proof law is provisions regarding evidence which include evidence, evidence, methods of collecting and obtaining evidence up to submitting evidence in court as well as the strength of evidence and burden of proof in criminal cases. Evidence in criminal procedural law is generally regulated in the Criminal Procedure Code, but in its development, the evidentiary provisions in the Criminal Procedure Code are distorted by the Corruption Crime Law. The Corruption Law in regulating its evidence uses the omkering van bewijslast principle or balanced proof. This research is compiled with a normative juridical research method and is structured to determine the principle of omkering van bewijslast in the legal theory of evidence and its regulation in the Indonesian Corruption Law.